Literature review: Interventions on health and education in the school context (Research, Society and Development, 2021)
Fostering health-related themes in the school environment is an essential pedagogical practice with regard to the living context of individuals in adolescence. It is important that the school faculty has the sensitivity to address the issue in the classroom with theoretical knowledge and a sense of acceptance of the anxieties brought by young students. In reflecting on this subject and all its nuances, there was a need to carry out a literature review study which aims to bring to light works related to interventions in school spaces related to health and its relationship with formal education. In order to appreciate and categorize the nature of the work carried out on the subject, a bibliographical study of a qualitative nature of 34 academic-scientific productions with Qualis/Capes A1 strata published between 2011 and 2020, which were published in nine national and international journals. From the reading of the articles, categories of analysis emerged that were treated by Bardin's Content Analysis, namely: (i) Health and School (ii) Adolescence and Health; and (iii) Adolescence and Health Risk Behavior. At the end of this work, the relationship established between health and education is considered important. It is from educational actions that a consistent attitude can be developed in relation to caring for the body and mind and, thus, promoting quality of life among Basic Education students.